Proton Transport Chains in Glucose Metabolism: Mind the Proton - Roosterman, Dirk; Meyerhof, Wolfgang; Cottrell, Graeme S. (Frontiers in Neuroscience, 2018)
The Emden-Meyerhof-Parnas pathway comprises eleven cytosolic enzymes interacting to metabolise glucose to lactic acid (CH3CH(OH)COOH). Glycolysis is largely considered as the conversion of glucose to pyruvate (CH3COCOO-). We consider glycolysis to be a cellular process and as such, transporters mediating glucose uptake and lactic acid release and enable the flow of metabolites through the cell, must be considered as part of the Emden-Meyerhof-Parnas pathway. In this review, we consider the flow of metabolites to be coupled to a flow of energy that is irreversible and sufficient to form ordered structures. This latter principle is highlighted by discussing that lactate dehydrogenase complexes irreversibly reduce pyruvate/H+ to lactate (CH3CH(OH)COO-), or irreversibly catalyze the opposite reaction, oxidation of lactate to pyruvate/H+. However, both lactate dehydrogenase complexes are considered to be driven by postulated proton transport chains. Metabolism of glucose to two lactic acids is introduced as a unidirectional, continuously flowing pathway. In an organism, cell membrane-located proton-linked monocarboxylate transporters catalyze the final step of glycolysis, the release of lactic acid. Consequently, both pyruvate and lactate are discussed as intermediate products of glycolysis and substrates of regulated crosscuts of the glycolytic flow.